Predictive Value and Prognostic Significance of Pan-Immune-Inflammation Value, Systemic Immune-Inflammation Index, and Systemic Inflammatory Response Index in Placenta Accreta Spectrum and Placenta Previa - Dayanan, Ruken; Filiz, Ahmet Arif; Aktemur, Gizem; Tokgoz Cakir, Betul; Karabay, Gulsan; Seyhanli, Zeynep; Ayas Ozkan, Merve; Duygulu Bulan, Dilara; Caglar, Ali Turhan (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVES: Placenta accreta spectrum (PAS) and placenta previa (PP) are major obstetric complications associated with significant maternal and perinatal morbidity. Inflammatory markers have been increasingly studied for their role in predicting adverse pregnancy outcomes. This study aims to evaluate the predictive and prognostic significance of the Pan-Immune-Inflammation Value (PIV), Systemic Immune-Inflammation Index (SII), Systemic Inflammation Response Index (SIRI), Neutrophil-to-Lymphocyte Ratio (NLR), Monocyte-to-Lymphocyte Ratio (MLR), and Platelet-to-Lymphocyte Ratio (PLR) in patients diagnosed with PAS and PP. STUDY DESIGN: A retrospective cohort study was conducted on pregnant women diagnosed with PAS and PP, along with a control group of healthy pregnancies. Preoperative inflammatory markers, including PIV, SII, SIRI, NLR, MLR, and PLR were analyzed. The predictive value of these indices for PAS was assessed using receiver operating characteristic (ROC) curve analysis, RESULTS: Inflammatory markers were significantly higher in PAS and PP cases (p<0.001). PIV demonstrated the highest predictive value (AUC=0.695, cut-off >692, sensitivity 69.3%, specificity 66.7%). SIRI (AUC=0.671, cut-off >2.76, sensitivity 58.7%, specificity 69.2%), SII (AUC=0.630, cut-off >1012, sensitivity 64%, specificity 57.7%), MLR (AUC=0.673, cut-off >0.3584, sensitivity 68%, specificity 60.3%), and PLR (AUC=0.612, cut-off >144.9, sensitivity 60%, specificity 62.8%) also showed predictive potential. CONCLUSION: PIV, SII, SIRI, MLR, and PLR are valuable inflammatory markers for predicting PAS and PP, with PIV demonstrating the highest diagnostic accuracy. These indices may serve as useful biomarkers for early risk stratification, potentially contributing to enhanced prenatal management and better-informed perinatal care in high-risk pregnancies.